2016
DOI: 10.1016/j.jinorgbio.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Osmocenyl-tamoxifen derivatives target the thioredoxin system leading to a redox imbalance in Jurkat cells

Abstract: ABSTRACT:To complete our study of the iron, ruthenium and osmium metallocene triad derived from hydroxytamoxifen, we report here the synthesis and study of the biological effects of two ferrocifen analogs in the osmium series, namely the monophenolic complex 1, the tamoxifen- within the cell and that inhibition of thioredoxin reductase is a key factor in rationalizing the cytotoxicity of these complexes on Jurkat cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…Therefore, their inhibition of the isolated and purified cytosolic isoform of thioredoxin reductase (TrxR1) was measured. In accordance with previous results, we tested the action of 1 and 2 alone, and the compounds obtained by enzymatic oxidation by the HRP/H 2 O 2 mixture of 1 and 2 , that is, 8 A and 10 , respectively. Compounds 1 and 2 only moderately inhibited cytosolic TrxR1 (IC 50 =19.36 μ m and 32.2 μ m , respectively), whereas 8 A and 10 were strong TrxR1 inhibitors (IC 50 =27 n m and 31 n m , respectively; Figure ).…”
Section: Resultsmentioning
confidence: 67%
“…Therefore, their inhibition of the isolated and purified cytosolic isoform of thioredoxin reductase (TrxR1) was measured. In accordance with previous results, we tested the action of 1 and 2 alone, and the compounds obtained by enzymatic oxidation by the HRP/H 2 O 2 mixture of 1 and 2 , that is, 8 A and 10 , respectively. Compounds 1 and 2 only moderately inhibited cytosolic TrxR1 (IC 50 =19.36 μ m and 32.2 μ m , respectively), whereas 8 A and 10 were strong TrxR1 inhibitors (IC 50 =27 n m and 31 n m , respectively; Figure ).…”
Section: Resultsmentioning
confidence: 67%
“…However, this inhibition was larger than that obtained with the corresponding quinine methides (IC 50 = 5.40 μM for 202 and 3.60 μM for 203 ). They found that the cytotoxicity of osmocifens depends on their oxidation within the cell and that inhibition of TrxR by oxidized species is a key factor in rationalizing the cytotoxic effects of these complexes on Jurkat cells . The authors also reported the inhibition of TrxR1 in vitro by the ansa‐ferrocifen derivative ( 204 , Figure ).…”
Section: Thioredoxin Reductase Inhibitorsmentioning
confidence: 99%
“…At the end of the incubation time, the culture medium was removed and adherent cells were detached, collected by centrifugation, then digested in HNO3. 36 . 37,38 This resolution is significantly better than that of classic FTIR spectromicroscopy, which is limited by the criterion of light diffraction (Abbe criterion) establishing the resolution limit at a level of /2.…”
Section: Quantification Of Metals In Cancer Cells By Icp-oesmentioning
confidence: 99%